2006
DOI: 10.1111/j.1365-3156.2006.01650.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in the prevalence and intensity of infection in Onchocerca volvulus microfilariae according to ethnicity and community after 8 years of ivermectin treatment on the island of Bioko, Equatorial Guinea

Abstract: Summary Bioko is the only island known in the world with endemic onchocerciasis. The island's rural communities consist of villages and cocoa plantations inhabited by Bubi and Fang ethnic groups. The aim of this study was to evaluate the impact of 8 years of vertical ivermectin distribution on the prevalence and intensity of Onchocerca volvulus infection in the rural population by means of pre‐ (1989) and post‐long term treatment (1998) epidemiological surveys. In both surveys, the entire population of 12 rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 15 publications
2
22
1
3
Order By: Relevance
“…Since 1987, this drug has been used in the treatment of filariae of medical significance such those of Onchocerca volvulus, M. perstans, and M. streptocerca in Africa. [31][32][33][34][35][36][37] However, there are few studies on the specific treatment of M. ozzardi with this drug. 1,18,19,38 This study confirmed the effectiveness of ivermectin in parasitologic blood clearance of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Since 1987, this drug has been used in the treatment of filariae of medical significance such those of Onchocerca volvulus, M. perstans, and M. streptocerca in Africa. [31][32][33][34][35][36][37] However, there are few studies on the specific treatment of M. ozzardi with this drug. 1,18,19,38 This study confirmed the effectiveness of ivermectin in parasitologic blood clearance of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Die einmalige Gabe von Ivermectin pro Jahr führte nach 6 Jahren in Nigeria zu einer Reduktion der MikrofilarienPrävalenz von Onchocerca von 70% zu 40% [28]; in Kamerun und Uganda nach 10 Jahren von 70% auf 7% [29], in Äquato-rialguinea nach 8 Jahren von 75% auf 38%, wobei dort große Unterschiede zwischen zwei Volksstämmen und zwischen einzelnen Gemeinden bestanden [30]. [16].…”
Section: Epidemiologieunclassified
“…A single administration of ivermectin per year led to a reduction in the prevalence of microfilariae of Onchocerca from 70 to 40% in Nigeria after 6 years [28]; in Cameroon and Uganda this figure was reduced from 70 to 7% after 10 years [29], and in Equatorial Guinea from 75 to 38% after 8 years, with significant differences between 2 ethnic tribes and individual communities [30]. Another study from Ghana reported that the prevalence of Onchocerca microfilariae doubled in 2 communities while the general infestation with microfilariae was reduced.…”
Section: Current Knowledge About the Pathogenmentioning
confidence: 99%